Flexible airway endoscopy in esophageal atresia patients undergoing colon interposition - Aliaa Rabie; Mohamed El Debeiky; Tamer Ghoneim; Ahmed Khairi; Ahmed Ezzat Mrzouk Saad El-Rouby (Egyptian Journal of Anaesthesia, 2021)
ABSTRACTBackground: Colon interposition is used for delayed surgical repair of esophageal atresia, but congenital esophageal atresia with or without tracheoesophageal fistula (CEA ± TEF) is associated with long-term respiratory morbidity. This study aimed to examine the prevalence of upper airway anomalies, and detect the implications of the preoperative flexible airway endoscopy (FAE) on the decision of performing tracheopexy whether aortopexy or more recently, posterior tracheopexy in cases of severe tracheomalacia. A randomized, prospective, controlled study was conducted in a tertiary care pediatric surgery center from September 2016 to October 2020 where thirty child of either sex, aged 2–8 years, scheduled for a colon interposition repair for esophageal atresia. After induction of general anesthesia dynamic airway endoscopic examination with ultra-thin fibroptic bronchoscopy was performedResults: Dynamic study of pediatric upper airway showed that only one case out of 30 child enrolled in the present study had grade II subglottic stenosis in the proximal trachea (3.34%), while five cases (16.67%) had tracheomalacia with different degrees and only one severe case required aortopexyConclusion: Dynamic airway endoscopic examination can predict airway anomalies associated with esophageal atresia and enhance post colon interposition respiratory outcomes.